Enhanced removal of humic substances in effluent organic matter from a leachate treatment system via biological upgradation of molecular structure - Chen, Mengfan (Environmental technology, 2022)
Biological upgradation (BU) process was proposed, with the goal of converting the molecular structure, for improving the coagulation effect on humic substances (HS) in effluent organic matter from the membrane bioreactor of a leachate treatment system. Enhancement of coagulation effect was observed with the improvement of chemical oxygen demand and HS removal efficiency from 45.5% and 56.5% to 80.0% and 92.6% (Fe dosage was 400 mg·L-1), respectively, which was approximately 30-40% higher than the other available researches. Variations in molecular weight (MW) and carboxyl contents of fulvic acid (FA) and humic acid (HA) were analysed by size exclusion chromatography coupled with dissolved organic carbon detection, potentiometric titration and Fourier transform infrared spectroscopy. The obtained results indicated that BU process led to the growth of MW of HS, of which the larger MW (1650 Da) FA and HA raised from 19.07 and 0.34 mgC·L-1 to 71.67 and 1.58 mgC·L-1, respectively, as well as increases in the carboxyl contents of FA and HA from 6.70 and 6.28 meq·gC-1 to 11.84 and 8.71 meq·gC-1, respectively. Because of this, a stronger binding effect between Fe and HS might be formed that improved the coagulation effect